Figuring the Relationship between Cash Dividend Ratio and Stock Price Crash in Companies Accepted in Tehran Stock Exchange - Ahadnezhad, Nadia; Azadi, Behnam; Imanzadeh, Peyman (International Journal of Economics and Financial Issues, 2018)
The present survey aims at instigating the relationship between cash dividend ratio and the risk of stock price crash of companies accepted in Tehran stock exchange. A statistical sample of 131 companies accepted in Tehran Stock Exchange was surveyed for the period between 2010 and 2015. In this study, Levin-Lin-Chu test is utilized to examine the fixity of variables. Also, Panel method with random effects are used to assess the significance of data. The results obtained from the survey hypothesis test are expressive of the fact that there is a significant reverse relationship between cash dividend ratio and the risk of stock price fallout. In other words, with the increase of cash dividend ratio, the risk of falling out stock prices decreases. Keywords: Cash dividend, risk of stock price crash, Tehran Stock Exchange JEL Classification: G32